EVALUASI KUALITAS FUNGSI INTERNAL AUDITOR DALAM MENINGKATKAN EFEKTIVITAS BANK - Sihwahjoeni Sihwahjoeni (Jurnal Keuangan dan Perbankan, 2011)
Internal auditor was a part that could not be separated from audit internal department. Internal auditor was theside considered having independency and high objectivity so it was expected to perform its task without pressurefrom anywhere. As the independent side, internal auditor was easier to see marks deviations done by managementparty related to their job result and the things related to internal control. Internal auditor had to be able maximallyto give the contribution for the increase and bank development. This research evaluated the internal auditorfunction implementation on banks, analyzed the contribution form given by internal auditor to a bank, anddescribed the bank trick to increase internal auditor quality to be able to give contribution to a bank. Frequentanalysis technique in this research was structural equation modelling (SEM) operated through AMOS 16 program.Based on analysis result, it showed that objectivity, performance and audit job, result communication, andaim, authority and accountability had a significant effect to a bank effectiveness, while independency, scope andinternal audit, profession efficiency, follow-up, and plan and operation did not have a significant effect towardbank effectiveness.